Implementation of quality measures and patient-reported outcomes in an epilepsy clinic. (26th November 2019) - Moura, Lidia M.V.R.; Magliocco, Brandon; Ney, John P.; Cheng, Eric M.; Esper, Gregory J.; Hoch, Daniel B.
Abstract : Objective: To see if systematic collection of patient-reported epilepsy quality measures can identify opportunities to improve care, and to examine the associations between these measures and physical and mental health. Methods: We developed a patient-reported questionnaire for medication adherence, seizure frequency, medication side effects, and driving that included the Patient-Reported Outcome Measurement Information System–10 (PROMIS-10) (physical and mental health). We offered it to all adult patients seen twice in an epilepsy clinic (January 2017–January 2018). The questionnaire was available on the web as well as a tablet provided at appointment check-in. We used the first completed questionnaire to explore the relationship between patient-reported care quality and measures of physical and mental health. Results: A total of 610 unique patients (15% of the total encounters) completed a survey. Respondents were comparable to nonrespondents. Respondents reported gaps in care or opportunities for quality improvement in 48.4% (n = 295) of the encounters. Of patients who reported at least 1 seizure per month over the previous 3 months, 55.2% (n = 100) reported problems with adherence, 30.0% (n = 131) reported having problems believed to be adverse reactions to anticonvulsants, and 15.2% (n = 41) reported driving. In addition, respondents who reported either seizures over the recent 3 months, nonadherence to treatment due to cost, or anticonvulsant-associated adverse effects had consistently worse physical and mental health (all p < 0.05). Conclusions: Systematic collection of epilepsy quality measures endorsed by the American Academy of Neurology can identify opportunities for quality improvement. Measures of epilepsy care quality predict outcomes that matter to patients.